Genetic diversity analysis of rice cultivars (Oryza sativa L.) differing in salinity tolerance based on RAPD and SSR markers - Kanawapee, Nantawan; Sanitchon, Jirawat; Srihaban, Pranee; Theerakulpisut, Piyada (Electronic Journal of Biotechnology, 2011)
Thirty rice cultivars were evaluated for salinity tolerance during the seedling stage and were divided into five tolerance groups including tolerant (T), moderately tolerant (MT), moderately susceptible (MS), susceptible (S) and highly susceptible (HS) which comprised 5, 10, 9, 4 and 2 cultivars respectively. Genetic diversity of all rice cultivars was evaluated using random amplified polymorphic DNA (RAPD) and simple sequence repeats (SSR) markers. The cultivars were evaluated for polymorphisms after amplification with 20 random decamer primers and 20 SSR primer pairs. A total of 161 RAPD markers and 190 SSR alleles were produced which revealed 68.94% and 89.47% polymorphism respectively. Mean genetic similarity coefficient was 0.82 for RAPD and 0.70 for SSR. Cluster analysis based on RAPD markers was effective in grouping cultivars based on their salt tolerance ability. Group IA1, IB and IV contained three T, three S and two HS rice cultivars respectively. The MT and MS cultivars which showed similar physiological responses to salinity were resolved into two groups: Group IA2 and Group II comprising ten and eight MT/MS cultivars respectively. Cluster analysis based on SSR markers separated rice cultivars into groups based on genetic relatedness which did not correspond to salinity tolerance level. The results from this study provided some useful implications for salt tolerance breeding programs. The evaluation of genetic similarity and cluster analysis together with salt tolerance ability provides some useful guides for assisting plant breeders in selecting suitable genetically diverse parents for the crossing program.